Strategies to improve the physicochemical properties of peptide‑based drugs - Lee, Michelle Felicia *; Poh, Chit Laa * (Springer, 2023)
Peptides are a rapid-growing class of therapeutics with unique and desirable physicochemical properties. Due to disadvantages such as low membrane permeability and susceptibility to proteolytic degradation, peptide-based drugs have limited bioavailability, a short half-life, and rapid in vivo elimination. Various strategies can be applied to improve the physicochemical properties of peptide-based drugs to overcome limitations such as limited tissue residence time, metabolic instability, and low permeability. Applied strategies including backbone modifcations, side chain modifcations, conjugation with polymers, modifcation of peptide termini, fusion to albumin, conjugation with the Fc portion of antibodies, cyclization, stapled peptides, pseudopeptides, cell-penetrating peptide conjugates, conjugation with lipids, and encapsulation in nanocarriers are discussed.